Apical Debris Extrusion with Conventional Rotary and Reciprocating Instruments - Saberi, Eshagh Ali; Ebrahimipour, Sediqe; Saberi, Mersad (Iranian Endodontic Journal, 2020)
Introduction: The aim of the present study was to compare the amount of apical debris extrusion after preparation using hand files, reciprocating files, and full rotary nickel-titanium systems. Methods and Materials: One hundred extracted human mandibular molars with two separated canals in mesial root were divided into five groups and prepared using reciprocating systems (Reciproc and Safesider endodontic reamer files), full rotary systems (Mtwo and Neoniti A1 files) and hand instrumentation systems. Endodontic access was prepared and a #15 K-file was passed beyond the apex of the mesiobuccal canal by 1 mm to ensure the canal patency. All mesiobuccal canals were prepared 1 mm shorter than the anatomic apex. In each case, extruded debris was collected in an Eppendorf tube and weighed after desiccation. The mean weight of extruded material was calculated in each group. The analysis was carried out using the Kruskal–Wallis test followed by two tailed and Mann-Whitney U test at a significance level of 0.05. The Bonferroni correction was also applied to correct multiple comparisons. Results: There was a statistically significant difference between the reciprocal and other techniques in debris extrusion (P<0.05). The order of groups ranked in terms of debris extrusion from the lowest to highest was as follows: 1) Hand instrumentation group (with crown down technique), 2) Mtwo group, 3) Neoniti A1 group, 4) Safesider endodontic reamer group, and 5) Reciproc group. Conclusion: Based on this in vitro study, all systems have some apical debris extrusion; however, using the hand instrumentation system resulted in extrusion of significantly less debris compared to the Reciproc group. It seems that hand and rotary instrumentation systems are better than reciprocating instrumentation systems in terms of the amount of debris extrusion. Keywords: Endodontics; Root Canal Preparation; Rotary Instrumentation